2016
DOI: 10.4103/1319-2442.174057
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in hemodialysis patients

Abstract: Erectile dysfunction (ED) is a common problem seen among patients on hemodialysis (HD), but it is still a taboo subject in our country. The attention given to this sexual problem remained low, and the prevalence of ED among these patients has not been well characterized. We carried out this study in order to determine the prevalence and severity of ED in HD patients. We conducted a descriptive cross-sectional study in our HD unit in March 2013. ED was evaluated using the International Index Erection Function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
1
12
1
1
Order By: Relevance
“…It was noted in this study that the prevalence of ED in males was lower (47.6%) as compared to the study done by Antonucci et al who reported 70% ED [3]. Gorsane et al reported 80% ED and Arslan et al recorded an 80.7% prevalence of ED in males undergoing hemodialysis [13,6]. However, it was intriguing to discover that studies conducted way back in the 1970s like Abram et al and those in the 1980s like Rodger et al also noted the same pattern where ED prevailed in more than 50% of the patients [14,15].…”
Section: Discussioncontrasting
confidence: 56%
“…It was noted in this study that the prevalence of ED in males was lower (47.6%) as compared to the study done by Antonucci et al who reported 70% ED [3]. Gorsane et al reported 80% ED and Arslan et al recorded an 80.7% prevalence of ED in males undergoing hemodialysis [13,6]. However, it was intriguing to discover that studies conducted way back in the 1970s like Abram et al and those in the 1980s like Rodger et al also noted the same pattern where ED prevailed in more than 50% of the patients [14,15].…”
Section: Discussioncontrasting
confidence: 56%
“…One of the side effects most frequently encountered with renal failure is known to be ED. ED may be identified at rates of 40% in male patients entering dialysis [14]. Different to what is known, study group included patients with no CKD diagnosis who were identified to experience problems related to erection.…”
Section: Discussionmentioning
confidence: 99%
“…У 19 (79,1 %) пациентов ЭД прогрессировала во время сеансов диализа. Помимо этого, ЭД не была связана с продолжительностью заместительной почечной терапии, уровнем гемоглобина и причиной почечной недостаточности при р = 0,765 и р = 0,441 соответственно [16].…”
Section: эректильная дисфункция у диализных больныхunclassified